Inhibitory effect of jengkol leaf (Pithecellobium jiringa) extract to inhibit Candida albicans biofilm - Muhammad Luthfi; Ira Arundina; Nizamiar Hamni (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Candida albicans (C. albicans) are dimorphic fungi in oral cavity, considered not only as normal flora, but also as pathogens. C. albicans have an ability to grow biofilm, which has a thick layer of outer skin structure, called as extracellular matrix. Jengkol leaves (Pithecellobium jiringa) contain alkaloids, flavonoids, terpenoids, and lectins, which have an ability as antifungal agent Purpose: This study aimed to analyze the optimum dose of jengkol leaf extract as antibiofilm against C. albicans biofilms. Method: C. albicans were cultured on yeast peptone dextrosa (YPD) media in 96-well microtiter plate flat bottom plates. There were one control group (without treatment) and three treatment groups. The first treatment group was given jengkol leaf extract at a dose of 100 mg/ ml. The second treatment group was given jengkol leaf extract at a dose of 200 mg/ ml. And, the third treatment group was given jengkol leaf extract at a dose of 400 mg/ ml. Semi quantitative method was applied to determine C. albicans biofilmsis using Crystal Violet staining technique. The absorbance of the cells then was calculated using a spectrophotometer with a wavelength of 570 nm. Result: The mean value of optical density in the control group was 1.23. The mean value of optical density in the treatment group with a dose of 100 mg/ ml was 0.2. Meanwhile, the mean value of optical density in the treatment group with a dose of 200 mg/ ml was 0.2, and 0.21 in the treatment group with a dose of 400 mg/ ml. The results also showed that there were significant differences between the control group and all of the treatment groups (p<0.05), but there was no significant difference between the treatment groups (p>0.05). Conclusion: The optimum dose of jengkol leaf extract used as antibiofilm against C. albicans biofilms is 100 mg /ml with an inhibitory percentage of 83.7%.